Pengaruh Koinduksi Anestesi Ketamin 0,4 mg/kgBB terhadap Hipotensi pada Induksi Anestesi dengan Propofol 2mg/kgBB - , dr. Joko Purnomo; , dr. Pandit Sarosa, Sp.An-K ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Induction anesthesia requirement for General Anesthesia. One of the drug option in induction is propofol, because in addition to the rapid onset also causes relaxation of airway muscles. However, propofol also caused a hipotension, especially if given quickly (15 seconds). So that require medication coinduction to prevent these hemodynamic impairment. Ketamine is a drug that has sympathomimetic effects which can inhibit the vasodilation of propofol. The aim of this study is to test the hypothesis that coinduction with ketamine 0.4 mg / kg create a more stable hemodynamic on propofol 2mg/kg induction than without coinduction. A prospective randomized double blind study will be perfomed in 114 healthy patients (ASA I or II) undergoing general anesthesia. Patients were randomly allocated into two groups to recieve coinduction with ketamin 0.4mg/kg as group K with subject of 57 patients and saline as group P with subject of 57 patients.Haemodynamic change afther induction will be compare between the groups. The data analysis by t-test, and p<0,05 considered significantly different.